Official year book of Australia : no. 59, 1973 - Australian Bureau of Statistics (Canberra : Australian Bureau of Statistics, 1973)
Vols. for 1973- include statistical data compiled by the Bureau under its earlier name: Commonwealth Bureau of Census and Statistics.
Keywords: Statistics -- Australia -- Periodicals; Statistics -- Australia -- yearbooks